Training for Outsourced Workers in Housekeeping Department - eveline meilinda tjahjadi (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2017)
The purpose of research is to know the management of â€œXâ€ Mall operational that happen in Training and Development division of Human Resource Department in PT â€œXâ€. The accomplishment of internship during three month intern learnt about actual training of housekeeping worker from Housekeeping Departement at â€œXâ€ Mall in Jakarta, start from create training proposal until do training evaluation. This study uses interviews were asked directly to the 50 participants who are outsourced workers in housekeeping department, the outcome of the interview to see and review, whether the training is effective for the participants.